Uji Aktivitas Antioksidan Ekstrak Etanol Biji Jambu Bol (Syzygium Malaccense (L.) Merr. & Perry) Dengan Metode 1,1-Diphenyl-2-Picryhidrazyl (DPPH) - Rosa Devitria; Mega Elfia; Manisha Tri Cahyani (LPPM Universitas Dharma Andalas, 2023)
Many plants include antioxidant chemicals in their blooms, leaves, and fruit. Antioxidants are substances that slow, stop, or stop the oxidation process. Various antioxidant chemicals have the capacity to block oxidative processes, allowing body cells to recover from oxidative damage. Malay apple has a lot of antioxidant and anti-inflammatory properties. Malay apple flesh, seeds, and leaves include phenolic chemicals, flavonoids, and carotenoids, all of which have antioxidant properties. The IC50 value will be used to measure the antioxidant activity of guava seed ethanol extract in this investigation. The seeds of the malay apple were extracted using the maceration process using ethanol as the solvent. The antioxidant activity of the concentrated extract was then determined using the 1,1-Diphenyl-2-Picryhydrazyl (DPPH) method, which uses a small, simple, fast, and easy sample to activate the antioxidant activity of natural substances. This study took place between April and May of 2022. The IC50 value was determined to be 3,511 ppm. The antioxidant activity in this study exhibits substantial antioxidant activity to fight free radicals, according to the IC50 value obtained.